Suomen sisällissota Wars Across the World: Finland 1918 -videopelissä - Walliander, Haron; Mähkä, Rami (Finland, 2025)
The article analyses the videogame Wars Across the World: Finland 1918 as a gamified representation of the Finnish Civil War of 1918.